KEBUTUHAN AIR BERSIH MASYARAKAT DI DAERAH PERDESAAN NELAYAN Di Wilayah Pesisir Kabupaten Pasir, Kalimantan Timur - Yudo, Satmoko; Hernaningsih, Taty (Jurnal Air Indonesia, 2006)
Coastal region is very potential area for developing in sectors of fish, low and middle business from domestic industrial such as: food and husbandary food, fish net and shipping, services, trasnportation and travel. Concerning to high conomical potency in this coastal area is expected to be supporting area for central activities. For this supporting in public facility require elictricity, road and sea transportation, telecommunication, housing, health and the important is water supply. In providing water supply infrastructure is needed good planning so that the result outcomes in right purpose and beneficial for certain community. One of the supporting in planning is to know social-economical condition of this community. This paper will show in general the result of coastal community social economy in Local Government, Pasir, East Kalimantan. Kata kunci : Masyarakat nelayan, perencanaan penyediaan air bersih, kondisi sosial-ekonomi penduduk pesisir.